GOVERNMENT PERFORMANCE PADA KEBIJAKAN TRANSFORMASI DIGITAL: BAGAIMANA TRANSFORMATION CAPABILITY MEMPENGARUHINYA? (STUDI EMPIRIS DI PROVINSI MALUKU UTARA) - Sulistiyo, Heru; Martua, Aleknaek; Sayuti, Sayuti; Mulyana, Mulyana; Ginting, Irka Tia (Fakultas Politik Pemerintahan IPDN, 2023)
Abstract Effective governance is now one of the key pillars in maintaining the stability and prosperity of a country. The development of information and communication technologies has fundamentally changed the way governments operate around the world. The digital age has opened up new opportunities and presented significant challenges in managing the country and serving the community. In 2021, North Maluku Province has officially established the Regional Digitalization Acceleration and Expansion Team (TP2DD). The program is expected to be a good start and a momentum to establish coordination, commitment, and synergy together in the context of expanding the digitization of local government transactions, to support national economic recovery which has a real impact on people's welfare. This study builds and empirically tests a model of the impact of government digital transformation on performance based on dynamic capability theory. This research uses a quantitative method approach. The research design used is a survey. The analysis method used is using a confirmatory factor analysis approach, namely Partial Least Squares - Structural Equation Modeling (PLS-SEM). From the results of empirical statistical testing on case studies in North Maluku Province in the implementation of digitalization in each regional apparatus, transformation capability directly affects government performance. Transformation capability directly affects partnering agility, although at the same time the research shows that partnering agility has not had a significant effect on government performance. So related to partnering agility, it is necessary to create a joint program holistically in order to increase partnering agility. The results of this study also provide ideas for further research to find out and analyze what factors can influence partnering agility to be achieved. Keywords: Government Performance, Partnering Agility, Transformation Capability, and Digital Transformation